Emergence of Multidrug- and Pandrug- Resistant Pseudomonas aeruginosa from Five Hospitals in Qatar - M.A. Sid Ahmed; A.A.I. Hassan; S. Abu Jarir; H. Abdel Hadi; D. Bansal; A. Abdul Wahab; M. Muneer; S.F. Mohamed; K. Zahraldin; J.M. Hamid; M.A. Alyazidi; M. Mohamed; et al. (Elsevier, 2019)
Summary: Background: A global rise in multidrug-resistant (MDR) nosocomial infections has led to a significant increase in morbidity and mortality. MDR Gram-negative bacteria (GNB) are recognised for rapidly developing drug resistance. Despite Pseudomonas aeruginosa being the second most common GNB isolated from healthcare associated infections, the magnitude of MDR P. aeruginosa (MDR-PA) has not been evaluated in Qatar. Aim: To assess the prevalence and antimicrobial susceptibility patterns of MDR-PA from 5 major hospitals in Qatar. Methods: A total of 2533 P. aeruginosa clinical isolates were collected over a one-year period. MDR-PA was defined as resistance to at least one agent of ≥ 3 antibiotic classes. Clinical and demographic data were collected prospectively. Findings: The overall prevalence of MDR-PA isolates was 8.1% (205/2533); the majority of isolates were from patients exposed to antibiotics during 90 days prior to isolation (85.4 %, 177/205), and the infections were mainly hospital-acquired (95.1%, 195/205) with only 4.9% from the community. The majority of MDR-PA isolates were resistant to cefepime (96.6%, 198/205), ciprofloxacin, piperacillin/tazobactam (91%, 186/205), and meropenem (90%, 184/205). Patient comorbidities with MDR-PA were diabetes mellitus (47.3%, n=97), malignancy (17.1%, n=35), end-stage renal disease (13.7%, n=28) and heart failure (10.7%, n=22). Conclusion: There was a significant prevalence of MDR-PA in Qatar, primarily from healthcare facilities and associated with prior antibiotic treatment. There was an alarming level of antimicrobial resistance to carbapenems. Our results are part of a national surveillance of MDR to establish effective containment plans. Keywords: Gram-negative bacteria, Antibiotic resistance, Antimicrobial susceptibility, Carbapenem, Cephalosporin, Hospital-acquired infections